A study on the relationship between Amanah Saham Mara returns and economic indicators / Rozina Ismail - Ismail, Rozina (1995)
Amanah Saham MARA Berhad is the second unit trust management company that has been established in Malaysia after the Asia Unit Trust (owned by Australian investors) and Amanah Saham MARA Berhad is the first unit trust management company that is established for the bumiputeras. The company's main objective is to encourage the bumiputeras to invest with a small capital and subsequently this capital will be invested in the capital market. Thus, it is appropriate to make a study of the returns of Amanah Saham MARA in relation with the economic indicators in order to maximise the unitholders' wealth without forgetting social responsibility. This study is about the Amanah Saham MARA returns in terms of dividends' distributions by each funds issued. It is aimed at providing a comprehensive analysis and model of returns by using dividends in facing changes of the economic indicators. The significant influences (effectiveness) and relationship between the economic indicators and the returns of Amanah Saham MARA are the major areas of the study. One major hypothesis has been tested in this study as to identify the relationship between the Amanah Saham MARA returns and the economic indicators. In this case, what type of relationship between the Amanah Saham MARA returns and the economic indicators and which economic indicators are the major influences on the Amanah Saham MARA returns. The major conclusion drawn from this study showed that there is a strong relationship between the Amanah Saham MARA returns and the economic indicators and only two of the economic indicators influenced the returns of Amanah Saham MARA at different level of confidence interval. By using these findings, the Amanah Saham MARA Berhad can sustain growth and performance by maintaining adequate portfolio investments to fulfil the unitholders required rate of return in according to economic changes. In this case, the Amanah Saham MARA Berhad should manage their funds consistent with their short term objectives and the primary objective of constrained unitholder's wealth maximisation.